ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM MEMILIH SMK MUHAMMADIYAH 1 YOGYAKARTA - Kamaludin - - (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study were to know infuance of the (1) marketing mix to (2)consumer decision-making in choosing a hight school. Implemented in SMK Muhammadiyah 1 Yogyakarta. The method used is the method of multiple linear regression analysis, using simulataneous test and partiak test. While data collection using questionnaire. Samples taken as many as 80 respondents using sample random sampling technique. The results showed the multiple linear regression model is Y = -3,960 + 0,188X1 + 0,221X2 + 0,208X3 + 0,189X4 + 0,492X5 + 0,287X6 + 0,230X7 That is, (X1)Product, (X2)Price, (X3)Promotion, (X4)Location, (X5)People, (X6)Physical Evidenece and (X7)Procces contributes greatly to the performance (Y)consumer decisions in choosing SMK Muhammadiyah 1 Yogyakarta. The magnitude of effect seen from the determination coefficient (R2). Value of the determinant coefficient (R2) was 0.767. The results show that the coefficient determinant of Product, Price, Promotion, Location, People, Physical Evidenece and Procces have a positive influence of consumer decisions in choosing SMK Muhammadiyah 1 Yogyakarta by 76.7% and the remaining 33.3% is influenced by other factors.